Real wage cyclicality of female stayers and movers in part-time and full-time jobs - Robert A. Hart (Institute for the Study of Labor (IZA), 2006)
Based on the British New Earnings Survey Panel Data for 1975-2001, this paper investigates the real hourly wage cyclicality of part-time and full-time females. Relative degrees of wage responsiveness are estimated in respect of job stayers, movers between jobs (involving either retaining part-time or full-time job status or switching from one to the other), and movers within existing jobs (switching between part-time and full-time status within the same job). The work also incorporates separate estimates of the probabilities of changing jobs for the various mover categories. It is shown that distinguishing between private and public sector employment is important to work along these lines.
urn:nbn:de:101:1-20090406345
Keywords: 330